N-acetyl-l-cysteine controls osteoclastogenesis through regulating Th17 differentiation and RANKL in rheumatoid arthritis - Kim, Hae-Rim; Kim, Kyoung-Woon; Kim, Bo-Mi; Lee, Kyung-Ann; Lee, Sang-Heon (The Korean journal of internal medicine, 2019)
Background/Aims This study aimed to determine the regulatory role of N-acetyl-l-cysteine (NAC), an antioxidant, in interleukin 17 (IL-17)-induced osteoclast differentiation in rheumatoid arthritis (RA). Methods After RA synovial fibroblasts were stimulated by IL-17, the expression and production of receptor activator of nuclear factor κ-B ligand (RANKL) was determined by real-time polymerase chain reaction and enzyme-linked immunosorbent assay (ELISA). Osteoclastogenesis was also determined after co-cultures of IL-17-stimulated RA synovial fibroblasts, Th17 cells and various concentrations of NAC with monocytes. After human peripheral CD4+ T cells were cultured with NAC under Th17 condition, IL-17, interferon γ, IL-4, Foxp3, RANKL, and IL-2 expression and production was determined by flow cytometry or ELISA. Results When RA synovial fibroblasts were stimulated by IL-17, IL-17 stimulated the production of RANKL, and NAC reduced the IL-17-induced RANKL production in a dose-dependent manner. NAC decreased IL-17-activated phosphorylation of mammalian target of rapamycin, c-Jun N-terminal kinase, and inhibitor of κB. When human peripheral blood CD14+ monocytes were cultured with macrophage colony-stimulating factor and IL-17 or RANKL, osteoclasts were differentiated, and NAC reduced the osteoclastogenesis. After human peripheral CD4+ T cells were co-cultured with IL-17-pretreated RA synovial fibroblasts or Th17 cells, NAC reduced their osteoclastogenesis. Under Th17 polarizing condition, NAC decreased Th17 cell differentiation and IL-17 and RANKL production. Conclusions NAC inhibits the IL-17-induced RANKL production in RA synovial fibroblasts and IL-17-induced osteoclast differentiation. NAC also reduced Th17 polarization. NAC could be a supplementary therapeutic option for inflammatory and bony destructive processes in RA.